The interaction between sleep patterns and oxidative balance scores on the risk of cognitive function decline: Results from the national health and nutrition examination survey 2011-2014. - Taiwei Lou; Zhiru Zhao; Hongjin Du; Jiwei Zhang; Tian Ni; Miaoran Wang; Qiuyan Li (PLoS ONE)
Background Unhealthy sleep and exposures to oxidative factors are both associated with poor cognitive performance (PCP), but limited evidence has been found regarding the relationship between sleep patterns and oxidative factor exposures independently or jointly with the risk of PCP. Methods We analyzed data from 2249 adults aged ≥60 years in the National Health and Nutrition Examination Survey (NHANES) database (2011-2014). Self-reported questionnaires were used to collect data on sleep duration and sleep disorder, categorizing sleep duration into three groups based on responses: short (6 hours or less per night), normal (7-8 hours per night), or long (9 hours or more per night). Sleep disorder were categorized into two groups: sleep disorder, non-sleep disorder. Oxidative balance score (OBS) was calculated based on 20 oxidative stress exposures related to diet and lifestyle factors, with higher scores indicating greater antioxidant exposures. Survey-based multivariable adjusted regression analyses were conducted to examine the associations between sleep patterns or OBS alone and in combination with overall and PCP risks. Results Compared to the normal sleep duration group, the long sleep duration group had a higher risk of PCP (DSST<34) (OR = 1.91, 95% CI = 1.05-3.48, P = 0.021); while OBS was negatively correlated with the risk of PCP (DSST<34) [Q4 vs Q1 (OR = 0.50, 95% CI = 0.29-0.92, P = 0.004)]. There was an interaction effect between sleep patterns (sleep duration, sleep disturbances) and OBS on PCP (DSST<34) (P = 0.002). Further stratified analysis showed that in individuals with normal sleep duration, long sleep duration, or no sleep disturbances, antioxidant exposures, compared to pro-oxidant exposures, reduced the risk of low cognitive function occurrence. Conclusions In older populations, unhealthy sleep patterns (especially excessive sleep duration) and low OBS alone or in combination increase the risk of cognitive decline. Healthy sleep and lifestyle habits rich in antioxidant factors are crucial for protecting cognitive function in older adults.